Analysis of lower-body dimensions and their implementation in compression garment development - Kasey Hatch; Carol McDonald; Anke Klepser; Kristina Brubacher; Simeon Gill (Communications in Development and Assembling of Textile Products, 2024)
This experimental study aims to develop an approach to quantify dimensional changes in the lower body of female football players, with the intention of demonstrating how the results can be used to inform the development of lower body sports compression garments. A framework was established in order to analyse 3D body scans in functional postures using Rhinoceros 3D® and Grasshopper as a response to the limitations of current scanner software. The outcome provides an alternative methodology to locate landmarks on the body and extract dimensions in various sporting postures. Suggestions have been made as to how this information can aid pattern making, sizing, and grading of sports compression leggings, that can provide the wearer with optimal clothing fit, pressure delivery and comfort.